High-performance hollow fiber membrane with open outer skin layer

By adding a large molecular weight hydrophilic polymer to the cast film liquid of the hollow fiber membrane and dissolving the area in the modification bath, the problem of low flux of the hollow fiber membrane is solved, and the preparation of a high-performance hollow fiber membrane is achieved.

CN119588192APending Publication Date: 2025-03-11SHANGHAI LEPURE BIOTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810849.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing hollow fiber membrane has a large penetration resistance and low flux, making it difficult to increase its flux while ensuring high retention rate.

Method used

By adding a large molecular weight hydrophilic polymer to the cast film liquid as a structural stabilizer and undergoing a modification bath treatment after solidification, the physical structure of the fiber outer wall is dissolved and reconstructed to form an open hollow fiber membrane outer skin layer.

Benefits of technology

The flux of the hollow fiber membrane is significantly improved, while ensuring high retention rate, forming a high-performance polysulfone hollow fiber membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588192A_ABST
    Figure CN119588192A_ABST
Patent Text Reader

Abstract

A preparation method of the high-performance hollow fiber membrane comprises the following steps: respectively preparing a membrane casting solution and a core solution, co-extruding the membrane casting solution and the core solution flowing in an annular membrane casting solution fluid from a spinning head to form a primary membrane filament, and curing the primary membrane filament through a coagulating bath; and performing modification bath and pure water rinsing to obtain the high-performance polysulfone hollow fiber membrane with the open outer skin layer. When the hollow fiber membrane is prepared, the large-molecular-weight hydrophilic polymer is added into the membrane casting solution to serve as a structure stabilizer, modification bath is introduced, an open hollow fiber membrane outer skin layer can be formed, the flux is remarkably improved while the retention rate of the membrane material is guaranteed, and therefore the high-performance polysulfone hollow fiber membrane is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-performance membrane materials, and in particular to a high-performance hollow fiber membrane with an open outer skin layer. Background Art

[0002] Hollow fiber membranes are mostly used for internal pressure filtration when separating high value-added materials (such as fluid materials in the biopharmaceutical field). Ideal hollow fiber membrane materials should have dense inner walls and low permeation resistance. Dense inner walls can effectively ensure a high recovery rate of the target (product in the concentrate) or a high retention rate of impurities (product in the permeate); low permeation resistance can improve the flux and efficiency of filtration separation. Since the formation of hollow fiber membranes is usually completed through the path of instantaneous phase separation of the casting liquid, the density of the inner and outer walls that are in direct contact with the non-solvent is often high, resulting in a large overall permeation resistance and low flux of the polysulfone hollow fiber membrane. On the premise of ensuring a high retention rate (or recovery rate), in order to improve the flux of the hollow fiber membrane, it is an effective way to give it an open outer skin.

[0003] From a process perspective, there are currently two main methods to reduce the density of the outer skin layer. One is that the nascent membrane filaments pass through a certain length of air segment (located above the surface of the coagulation bath) before entering the coagulation bath, which is called the "dry segment". This method is also called the "dry-wet" method. The water vapor in the air segment can cause the outer wall of the nascent membrane filament to form pores and pre-gel, which is conducive to the formation of a relatively open outer skin layer. However, the humidity of the air segment is usually difficult to accurately control or the control cost is high, and humidity fluctuations will have an adverse effect on stable production. Another method is to use a single-stage solvent-non-solvent mixed coagulation bath. The presence of solvent in the coagulation bath will inhibit the diffusion of solvent in the nascent membrane filaments into the coagulation bath, thereby keeping the interface concentration of the polymer at the outer skin layer at a relatively low level. However, considering that the main function of the above-mentioned single-stage coagulation bath is to promote the solidification and molding of the nascent membrane filaments, the proportion of solvent should not be too high, and the degree of openness of the formed outer skin layer is limited. In summary, it is necessary to develop a new and effective strategy to induce the formation of hollow fiber membranes with open outer skin layers. Summary of the invention

[0004] The object of the present invention is to overcome at least one disadvantage of the prior art and provide a high-performance hollow fiber membrane with an open outer skin layer.

[0005] The technical solution adopted by the present invention is: The present invention provides a high-performance hollow fiber membrane with an open outer skin layer, and the preparation method thereof comprises the following steps: Prepare a casting solution and a core solution respectively, wherein the casting solution comprises a high molecular polymer, a structural stabilizer, a pore-forming additive and an organic solvent, wherein the high molecular polymer is selected from at least one of polysulfone, polyetheretherketone, polyethersulfone and polyethersulfoneketone, and the structural stabilizer is a hydrophilic polymer with a molecular weight of not less than 300 kD; The casting liquid and the core liquid flowing in the annular casting liquid fluid are co-extruded from the spinning head to form primary membrane filaments, and the primary membrane filaments are solidified in a coagulation bath; and then in a modification bath and pure water rinse to obtain the high-performance polysulfone hollow fiber membrane with an open outer skin layer; The modification bath consists of an organic solvent and water, wherein the volume proportion of the organic solvent is 70% to 90% and the rest is pure water.

[0006] In some examples, the casting solution comprises by weight percentage: 17% to 23% high molecular polymer, 6% to 12% structural stabilizer, 3% to 6% porogenic additive, and the rest is organic solvent.

[0007] In some examples, the volume proportion of the organic solvent in the coagulation bath does not exceed 30%, and the rest is pure water.

[0008] In some examples, the volume proportion of the organic solvent in the core liquid is no more than 30%, the rest is pure water, and the core liquid temperature is 25-50°C.

[0009] In some examples, the organic solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0010] In some examples, the structural stabilizer is selected from at least one of polyethylene glycol with a molecular weight of 300 kD to 600 kD and polyvinyl pyrrolidone with a molecular weight of 300 kD to 500 kD. In some examples, the porogen is selected from at least one of lithium chloride, lithium nitrate, and sodium nitrate.

[0011] In some examples, the modification bath treatment time is 4 to 6 seconds.

[0012] In some examples, the temperature of the modification bath is 25-50°C.

[0013] In some examples, the temperature of the coagulation bath is 25-50°C.

[0014] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0015] The beneficial effects of the present invention are: Some examples of hollow fiber membranes of the present invention: (1) The newly formed hollow fiber membrane filaments pass through a coagulation bath and then enter a modification bath. The organic solvent with a higher concentration in the modification bath can dissolve the outer skin of the fiber in a limited area, causing some polymers to fall off while reconstructing the physical structure of the outer wall of the fiber, thereby forming an open outer skin of the hollow fiber membrane; the degree of limited dissolution and reconstruction can be finely controlled by adjusting the solvent volume ratio, temperature and time of the fiber passing through the modification bath. (2) A high molecular weight hydrophilic polymer is added to the casting liquid as a structural stabilizer, which can be physically entangled with the polymer in the membrane matrix to prevent the hollow fiber membrane from being excessively dissolved in the modification bath, resulting in too much polymer falling off from the matrix, effectively ensuring the stability of the physical structure of the hollow fiber membrane. Therefore, the formation of an open outer skin of the hollow fiber membrane requires the cooperation of the modification bath and the structural stabilizer in the casting liquid. (3) The technical process provided by the present invention can be realized by adding an additional liquid tank between the coagulation bath tank and the pure water rinsing tank of the traditional production line, which is convenient for process updating. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Comparison of hollow fiber membrane morphology between Example 4 and Comparative Example 5. DETAILED DESCRIPTION

[0017] A high-performance hollow fiber membrane with an open outer skin layer, the preparation method of which comprises the following steps: Prepare a casting solution and a core solution respectively, wherein the casting solution comprises a high molecular polymer, a structural stabilizer, a pore-forming additive and an organic solvent, wherein the high molecular polymer is selected from at least one of polysulfone, polyetheretherketone, polyethersulfone and polyethersulfoneketone, and the structural stabilizer is a hydrophilic polymer with a molecular weight of not less than 300 kD; The casting liquid and the core liquid flowing in the annular casting liquid fluid are co-extruded from the spinning head to form primary membrane filaments, and the primary membrane filaments are solidified in a coagulation bath; and then in a modification bath and pure water rinse to obtain the high-performance polysulfone hollow fiber membrane with an open outer skin layer; The modification bath consists of an organic solvent and water, wherein the volume proportion of the organic solvent is 70% to 90% and the rest is pure water.

[0018] In some examples, the casting solution comprises by weight percentage: 17% to 23% high molecular polymer, 6% to 12% structural stabilizer, 3% to 6% porogenic additive, and the rest is organic solvent.

[0019] In some examples, the volume proportion of the organic solvent in the coagulation bath does not exceed 30%, and the rest is pure water.

[0020] In some examples, the volume proportion of the organic solvent in the core liquid is no more than 30%, the rest is pure water, and the core liquid temperature is 25-50°C.

[0021] In some examples, the organic solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide. These solvents have good solubility for polysulfone, polyetheretherketone, polyethersulfone, and polyethersulfoneketone, and are better choices.

[0022] In some examples, the structural stabilizer is selected from at least one of polyethylene glycol with a molecular weight of 300 kD to 600 kD and polyvinyl pyrrolidone with a molecular weight of 300 kD to 500 kD. These structural stabilizers are easy to obtain, have good water solubility, and are more conducive to obtaining uniform hollow fiber membranes.

[0023] There is no particular requirement for the type of pore-forming additive, and it can be a conventional choice in the art. In some examples, the pore-forming additive is selected from at least one of inorganic salt pore-forming additives such as lithium chloride, lithium nitrate, and sodium nitrate. These pore-forming additives will not react with the structural stabilizer used, so that the hollow fiber membrane In some examples, the modification bath treatment time is 4 to 6 seconds, preferably 5 seconds. The short-term modification bath treatment can effectively dissolve the outer skin layer in a limited area to obtain a hollow fiber membrane with an open outer skin layer, while not damaging the structure of the inner skin layer.

[0024] In some examples, the temperature of the modification bath is 25-50° C. The temperature can be adjusted accordingly according to the pore size. Generally speaking, the higher the temperature, the more favorable it is to obtain a hollow fiber membrane with larger pores.

[0025] In some examples, the temperature of the coagulation bath is 25-50°C.

[0026] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0027] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0028] In each embodiment and comparative example of the present invention, the casting liquid is called primary membrane filament after being extruded from the spinning head, and its formation depends on the core liquid and the coagulation bath at the same time. The core liquid flows inside the annular casting liquid fluid to form a hollow channel. The primary membrane filament passes through the coagulation bath tank-modification bath tank-pure water rinsing tank in sequence, and then is stretched, wound and collected. The collected membrane filaments are placed in a glycerol aqueous solution and fully immersed, and then dried for the preparation of the filtration test assembly.

[0029] Preparation of test assembly: The hollow fiber membrane was installed in a custom housing and capped with epoxy resin to obtain a hollow fiber filtration test assembly.

[0030] The specific operation details are as follows: The polysulfone casting solution is prepared by heating and stirring a mixture of dry polysulfone (mass fraction 17% to 23%), a structural stabilizer (mass fraction 6% to 12%), a pore-forming additive (mass fraction 3% to 6%) and an organic solvent; after stirring, the mixture needs to be cooled and vacuum degassed before the membrane can be prepared.

[0031] Selection range of structural stabilizers: high molecular weight hydrophilic polymers, including polyethylene glycol (PEG) with a molecular weight of 300 kD to 600 kD, and polyvinylpyrrolidone (PVP) with a molecular weight of 300 to 500 kD; selection range of pore-forming additives: inorganic salts, including lithium chloride (LiCl), lithium nitrate (LiNO3), and sodium nitrate (NaNO3); selection range of organic solvents: N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc).

[0032] Core liquid (flowing out from the spinning head together with the casting liquid): pure water or a mixed solution of pure water and an organic solvent in a certain volume ratio; if it is a mixed solution, the volume proportion of the organic solvent is not higher than 30%; the core liquid temperature is 25-50°C.

[0033] Coagulation bath: pure water or a mixed solution of pure water and an organic solvent in a certain volume ratio; if it is a mixed solution, the volume proportion of the organic solvent shall not exceed 30%; the coagulation bath temperature is 25-50°C.

[0034] Modification bath: a mixed solution of pure water and organic solvent prepared in a certain volume ratio, wherein the volume proportion of organic solvent ranges from 70% to 90%; the modification bath temperature is 25 to 50°C, and the treatment time is 5s.

[0035] When the polysulfone concentration in the casting solution is the same, the membrane performance (including pure water flux and interception rate) is compared. Priority is given to ensuring the interception rate. When the interception rates are similar, the higher the pure water flux, the better the membrane performance, and the corresponding process is optimal.

[0036] Specific preparation parameters and performance tests are shown in Tables 1 to 3.

[0037] Table 1

[0038] In Table 1, the amount of high molecular polymer added is 17 wt.%, the volume proportion of organic solvent in the core liquid is 30%, the volume proportion of organic solvent in the coagulation bath is 30%, and the volume proportion of organic solvent in the modification bath is 90%. The organic solvent is NMP. The temperature of the core liquid, coagulation bath, and modification bath is 50°C, and "-" means no addition. Comparative Examples 1 and 2 were not treated with modification baths. The volume proportion of organic solvent in the modification bath used in Comparative Example 5 was 60%. The retentate is 100 kD PEG, and the unit of pure water flux is L·m-2 ·h -1 bar -1 .

[0039] From the test results in Table 1, we can see that: Compared with Comparative Example 1, the difference in the preparation of the hollow fiber membranes in Examples 1 to 5 mainly lies in the application of the structural stabilizer and the modified bath. Comparative Example 1 can actually be regarded as a conventional membrane preparation method. While ensuring the interception rate, the flux of Examples 1 and 2 is significantly improved, which reflects the superiority of the technical solution. From the comparison of Examples 1 to 5, it can be seen that the type of high molecular polymer has basically no significant effect on the pure water flux and interception rate of the hollow fiber membrane.

[0040] Compared with Example 2, the difference in the preparation of the hollow fiber membrane in Example 1 and Example 2 is mainly whether the modified bath treatment is performed. The polyethylene glycol retention rates of Example 1, Example 2 and Comparative Example 2 are similar, but the pure water flux of Example 1 and Example 2 is significantly higher than that of Comparative Example 2, indicating that the modified bath optimizes the outer skin layer of the hollow fiber and improves the permeability of the membrane.

[0041] Compared with Example 3, the difference in the preparation of the hollow fiber membrane in Example 1 and Example 2 is mainly the use of a structural stabilizer. Although the pure water flux of Comparative Example 3 is higher than that of Example 1 and Example 2, the retention rate of polyethylene glycol in Comparative Example 3 is significantly reduced. This shows that the structural stabilizer and the modified bath have a synergistic effect, and the structural stabilizer can well stabilize the structure of the hollow fiber membrane, avoid destroying the integrity of the endothelial layer, and thus ensure the retention performance of the hollow fiber membrane.

[0042] Compared with Example 4, the difference in the preparation of the hollow fiber membrane in Example 1 and Example 2 is mainly the molecular weight of the structural stabilizer. Although the pure water flux of Comparative Example 4 is higher than that of Example 1 and Example 2, the retention rate of polyethylene glycol in Comparative Example 4 is significantly reduced. This shows that the molecular weight of the structural stabilizer has an unpredictable effect on the performance of the hollow fiber membrane. The hydrophilic polymer with a small molecular weight cannot effectively stabilize the structure of the hollow fiber membrane, which will cause the retention performance of the prepared hollow fiber membrane to be significantly reduced. The abnormally high pure water flux indicates that the permeability of the hollow fiber membrane has increased significantly and it can no longer be used as a filter membrane.

[0043] Comparison of Examples 1 to 5 with Comparative Example 5 shows that the proportion of organic solvent in the modified bath is relatively low, resulting in insufficient localized dissolution of the outer skin layer. Compared with Comparative Example 2, the pure water flux of Comparative Example 5 is slightly increased, and the retention rate is basically unchanged.

[0044] Table 2

[0045] In Table 2, the amount of polymer added is 20 wt.%, the volume proportion of organic solvent in the core liquid is 10%, the volume proportion of organic solvent in the coagulation bath is 10%, and the volume proportion of organic solvent in the modification bath is 80%. The organic solvent is DMF. The temperature of the core liquid, coagulation bath, and modification bath is 35°C. "-" means no addition. Comparative Examples 6 and 7 are not treated with modification baths. The volume proportion of organic solvent in the modification bath used in Comparative Example 5 is 60%. The retentate is 20 kD PEG, and the unit of pure water flux is L·m -2 ·h -1 bar -1 .

[0046] From the test results in Table 2, we can see that: Compared with Example 4 and Comparative Example 8, the difference in the preparation of the hollow fiber membrane is mainly the molecular weight of the structural stabilizer. Both have significant differences in polyethylene glycol retention rate and pure water flux. It shows that the molecular weight of the structural stabilizer has an unpredictable effect on the hollow fiber membrane. The hydrophilic polymer with a small molecular weight cannot effectively stabilize the structure of the hollow fiber membrane, which will cause the retention performance of the prepared hollow fiber membrane to decrease significantly. The abnormally high pure water flux indicates that the permeability of the hollow fiber membrane has increased significantly and can no longer be used as a filter membrane.

[0047] Compared with Comparative Example 6, the difference in the preparation of hollow fiber membranes in Examples 6 to 10 is mainly the application of structural stabilizers and modified baths. Comparative Example 6 can actually be regarded as a conventional membrane preparation method. Examples 6 and 7 significantly improve the flux while ensuring the interception rate, which reflects the superiority of this technical solution. From the comparison of Examples 6 to 5, it can be seen that the type of high molecular polymer has basically no significant effect on the pure water flux and interception rate of the hollow fiber membrane.

[0048] Compared with Comparative Example 7, the difference in the preparation of the hollow fiber membranes in Examples 6 and 7 is mainly whether the modified bath treatment is performed. The polyethylene glycol retention rates of Examples 6 and 7 are similar to those of Comparative Example 7, but the pure water flux of Examples 6 and 7 is significantly higher than that of Comparative Example 7, indicating that the modified bath optimizes the outer skin layer of the hollow fiber and improves the permeability of the membrane.

[0049] Compared with Example 8, the difference in the preparation of the hollow fiber membrane in Example 6 and Example 7 is mainly the use of a structural stabilizer. Although the pure water flux of Comparative Example 8 is higher than that of Example 6 and Example 7, the retention rate of polyethylene glycol in Comparative Example 8 is significantly reduced. This shows that the structural stabilizer and the modified bath have a synergistic effect, and the structural stabilizer can stabilize the structure of the hollow fiber membrane well, avoid destroying the integrity of the endothelial layer, and thus ensure the retention performance of the hollow fiber membrane.

[0050] Compared with Example 9, the difference in the preparation of hollow fiber membranes in Example 6 and Example 7 is mainly the molecular weight of the structural stabilizer. Although the pure water flux of Comparative Example 9 is higher than that of Example 6 and Example 7, the retention rate of polyethylene glycol in Comparative Example 9 is significantly reduced. This shows that the molecular weight of the structural stabilizer has an unpredictable effect on the performance of the hollow fiber membrane. The hydrophilic polymer with a small molecular weight cannot effectively stabilize the structure of the hollow fiber membrane, which will cause the retention performance of the prepared hollow fiber membrane to be significantly reduced. The abnormally high pure water flux indicates that the permeability of the hollow fiber membrane has increased significantly and it can no longer be used as a filter membrane.

[0051] Comparison of Examples 6 to 10 with Comparative Example 10 shows that the proportion of organic solvent in the modified bath is relatively low, resulting in insufficient confined dissolution of the outer skin layer. Compared with Comparative Example 7, the pure water flux of Comparative Example 10 is slightly increased, and the retention rate is basically unchanged.

[0052] Table 3

[0053] In Table 3, the amount of polymer added is 23 wt.%, the core liquid is pure water, the coagulation bath is pure water, the volume proportion of organic solvent in the modification bath is 70%, and the organic solvent is DMAc. The temperature of the core liquid, coagulation bath, and modification bath is 25°C, "-" means no addition, comparative examples 11 and 12 are not treated with modification baths, and the volume proportion of organic solvent in the modification bath used in comparative example 15 is 60%. The intercept is 5 kD PEG, and the unit of pure water flux is L·m -2 ·h -1 bar -1 .

[0054] From the test results in Table 3, we can see that: Compared with Comparative Example 11, the difference in the preparation of the hollow fiber membrane in Examples 11 to 15 is mainly the application of the structural stabilizer and the modified bath. Comparative Example 11 can actually be regarded as a conventional membrane making method. While ensuring the interception rate, the flux of Examples 11 and 12 is significantly improved, which reflects the superiority of the technical solution. From the comparison of Examples 11 to 5, it can be seen that the type of high molecular polymer has basically no significant effect on the pure water flux and interception rate of the hollow fiber membrane.

[0055] Compared with Comparative Example 12, the difference in the preparation of the hollow fiber membranes in Examples 11 and 12 is mainly whether the modified bath treatment is performed. The polyethylene glycol retention rates of Examples 11 and 12 are similar to those of Comparative Example 12, but the pure water flux of Examples 11 and 12 is significantly higher than that of Comparative Example 12, indicating that the modified bath optimizes the outer skin layer of the hollow fiber and improves the permeability of the membrane.

[0056] Compared with Example 11 and Example 12 and Comparative Example 13, the difference in the preparation of the hollow fiber membrane mainly lies in the use of a structural stabilizer. Although the pure water flux of Comparative Example 13 is higher than that of Example 11 and Example 12, the retention rate of polyethylene glycol in Comparative Example 13 is significantly reduced. This shows that the structural stabilizer and the modified bath have a synergistic effect, and the structural stabilizer can well stabilize the structure of the hollow fiber membrane, avoid destroying the integrity of the endothelial layer, and thus ensure the retention performance of the hollow fiber membrane.

[0057] Compared with Example 14, the difference in the preparation of the hollow fiber membrane in Example 11 and Example 12 is mainly the molecular weight of the structural stabilizer. Although the pure water flux of Comparative Example 14 is higher than that of Example 11 and Example 12, the retention rate of polyethylene glycol in Comparative Example 14 is significantly reduced. This shows that the molecular weight of the structural stabilizer has an unpredictable effect on the performance of the hollow fiber membrane. The hydrophilic polymer with a small molecular weight cannot effectively stabilize the structure of the hollow fiber membrane, which will cause the retention performance of the prepared hollow fiber membrane to be significantly reduced. The abnormally high pure water flux indicates that the permeability of the hollow fiber membrane has increased significantly and it can no longer be used as a filter membrane.

[0058] Comparison of Examples 11 to 15 with Comparative Example 15 shows that the proportion of organic solvent in the modified bath is relatively low, resulting in insufficient confined dissolution of the outer skin layer. Compared with Comparative Example 12, the pure water flux of Comparative Example 15 is slightly increased, and the retention rate is basically unchanged.

[0059] Figure 1 The morphology of the hollow fiber membranes of Example 4 and Comparative Example 5 is compared. Figure 1 It can be seen that through the process provided by the present invention, the openness of the outer skin layer of the hollow fiber membrane is significantly improved.

[0060] By comparing the comparative examples with the embodiments, it can be concluded that when preparing hollow fiber membranes, adding a high molecular weight hydrophilic polymer as a structural stabilizer to the casting solution and introducing a modified bath can form an open outer cortex of the hollow fiber membrane, which can significantly improve the flux while ensuring the retention rate of the membrane material, thereby preparing a high-performance polysulfone hollow fiber membrane.

[0061] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A high-performance hollow fiber membrane with an open outer skin layer, characterized in that: The preparation method thereof comprises the following steps: Prepare a casting solution and a core solution respectively, wherein the casting solution comprises a high molecular polymer, a structural stabilizer, a pore-forming additive and an organic solvent, wherein the high molecular polymer is selected from at least one of polysulfone, polyetheretherketone, polyethersulfone and polyethersulfoneketone, and the structural stabilizer is a hydrophilic polymer with a molecular weight of not less than 300 kD; The casting liquid and the core liquid flowing in the annular casting liquid fluid are co-extruded from the spinning head to form primary membrane filaments, and the primary membrane filaments are solidified in a coagulation bath; and then in a modification bath and pure water rinse to obtain the high-performance polysulfone hollow fiber membrane with an open outer skin layer; The modification bath consists of an organic solvent and water, wherein the volume proportion of the organic solvent is 70% to 90% and the rest is pure water.

2. The high performance hollow fiber membrane according to claim 1, characterized in that: The casting solution is composed of 17% to 23% of high molecular polymer, 6% to 12% of structural stabilizer, 3% to 6% of pore-forming additive, and the rest is organic solvent.

3. The high performance hollow fiber membrane according to claim 1, characterized in that: The volume proportion of the organic solvent in the coagulation bath does not exceed 30%, and the rest is pure water.

4. The high performance hollow fiber membrane according to claim 1, characterized in that: The volume proportion of organic solvent in the core liquid is no more than 30%, and the rest is pure water; and / or the core liquid temperature is 25-50°C.

5. The high performance hollow fiber membrane according to any one of claims 1 to 4, characterized in that: The organic solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

6. The high performance hollow fiber membrane according to claim 1, characterized in that: The structural stabilizer is selected from at least one of polyethylene glycol with a molecular weight of 300 kD to 600 kD and polyvinyl pyrrolidone with a molecular weight of 300 kD to 500 kD.

7. The high performance hollow fiber membrane according to claim 1, characterized in that: The porogen is selected from at least one of lithium chloride, lithium nitrate and sodium nitrate.

8. The high performance hollow fiber membrane according to any one of claims 1 to 4, characterized in that: The treatment time of the modification bath is 4 to 6 seconds.

9. The high performance hollow fiber membrane according to claim 8, characterized in that: The temperature of the modification bath is 25-50°C.

10. The high performance hollow fiber membrane according to any one of claims 1 to 4, characterized in that: The temperature of the coagulation bath is 25-50°C.